New light through old windows: nurses, colonists and indigenous survival. Issue 3 (28th September 2012) - McKillop, Ann; Sheridan, Nicolette; Rowe, Deborah
<x xml:space="preserve">Abstract</x> The aim of this study was to explore the influences, processes and environments that shaped the practice of European nurses for indigenous New Zealand (NZ) Māori communities who were being overwhelmed by introduced infectious diseases. Historical data were accessed from multiple archival sources and analysed through the lens of colonial theory. Through their work early last century, NZ nurses actively gained professional status and territory through their work with Māori. By living and working alongside Māori, they learned to practise in new ways that influenced Māori health. By developing a new role in new professional territory, nurses extended their practice to include health promotion as well as disease prevention. Māori survival from epidemics improved, and the population grew over that period. For Māori, however, Eurocentric care alleviated their immediate health problems, but the detrimental impact of the mechanisms of colonisation overall has continued to the present day.